IMPLEMENTATION OF FIREWALL MANGEL ON NETWORKS IN SMK ASSODIQIYAH SEMARANG - Putra, Toni Wijanarko Adi; Widodo, Muchamad (Jurusan Teknologi Informasi Universitas Semarang, 2023)
This study aims to regulate bandwidth usage and monitor website access using MikroTik. Bandwidth regulation with the aim of equalizing internet use where the number of students and teachers is 500 people, while monitoring websites and blocking negative websites aims to limit student access, which amounts to 416 students, consisting of 120 junior high school students, 150 vocational high school students, and 150 students. SD 100 and students 66 people. This research was conducted at Asshodiqiyah Vocational School as a technology base in the school environment under the Asshodiqiyah Foundation. The Assodiqiyah Foundation oversees elementary, junior high, and vocational schools and accommodates foreign students as boarding students. The service location is located at Jl. Sawah Besar Timur No 99 Rt.9 Rw. 2 Kaligawe Village, Gayamsari District, Semarang City. The method used in this research is Research and Development (R&D) [4]. This research discusses how to create and implement to the public how to use the Mikrotik tool as a regulator of bandwidth usage and see the sites that are accessed and if necessary block sites that are considered less suitable for students to access. The expected result is an even use of internet bandwidth and security of site access from negative things. So that students will avoid the negative influences that exist from the internet.